Efficient photocatalytic degradation of methylene blue over BiVO4/TiO2 nanocomposites. Issue 4 (May 2015) - Wetchakun, Natda; Chainet, Surachai; Phanichphant, Sukon; Wetchakun, Khatcharin
Abstract: BiVO4 /TiO2 nanocomposites were successfully synthesized by coupling the modified sol-gel method with hydrothermal method. The samples were physically characterized X-ray diffraction, scanning electron microscopy, transmission electron microscopy, Brunauer, Emmett and Teller (BET)-specific surface area, UV–vis diffuse reflectance spectrophotometry, zeta potential, and photoluminescence techniques. The BiVO4 /TiO2 nanocomposites exhibited good photocatalytic activity in degradation of methylene blue under simulated solar light irradiation. The photodegradation of methylene blue demonstrated that 0.5BiVO4 /0.5TiO2 photocatalyst exhibited much enhanced photoactivity than pure BiVO4 and TiO2 . Based on the obtained results, the as-prepare BiVO4 / TiO2 nanocomposite possessed great adsorptivity of methylene blue, extended light adsorption range, and efficient charge separation properties. Overall, this work could provide new insights into the fabrication of a BiVO4 /TiO2 composite as high performance photocatalyst and promise as a solar light photocatalyst for dye wastewater treatment.